Clinico-demographic feature of anemic pregnant women attending for antenatal checkup at a tertiary care hospital - Dharma Datta Subedi,; Nishanta Mishra, (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Anemia during pregnancy is a common and significant public health issue, leading to maternal and fetal complications, particularly in low- and middle-income countries. Understanding the clinico-demographic characteristics of anemic pregnant women can provide insights for targeted interventions and improve maternal health outcomes. The study was aimed to assess the clinico-demographic features of anemic pregnant women attending antenatal checkups at a tertiary care hospital in Madhesh Province, Nepal. Materials and Methods: A hospital based an analytical observational study with a prospective a cross-sectional study was conducted among pregnant women attending the antenatal clinic of a tertiary care hospital in Madhesh Province from July 2023 to June 2024. A total of 87 anemic pregnant women were included in the study. Data were collected through structured interviews, medical records, and laboratory results. Clinico-demographic variables such as age, education level, occupation, socioeconomic status, gestational age, parity, history of anemia, nutritional status, and laboratory results for hemoglobin levels were analyzed. The data were analyzed using SPSS version 20. Chi-square test was performed to find out the factors associated with anemia at 95% confidence interval. Results: Among 87 anemic pregnant women, 52 (59.77%) were mildly anemic, whereas 31 (35.6%) were moderately anemic and 4(4.59%) were severely anemic. Regarding, analysis of clinical symptoms 26 (29.88%) complained of dizziness and 11(12.64%) had palpitation. Clinical sign showed 37 (42.5%) had pallor. Analysis of anemic women in relation to age group was statistically significant and P value 0.02. Among illiterate women 25 (71.4%) had moderate to severe anemia, whereas among literate women had 10 (19.2%) moderates to severe anemia. Birth spacing helps to decrease severity of anemia. Among total 22 multi gravida females with moderate to severe anemia < 2 years of birth spacing were 20 (80.0%) and birth spacing > 2 years were 2 (11.8%). Conclusion: Clinico-demographic factors such as age, education, parity, and nutritional status were strongly associated with anemia in pregnancy. There is a need for enhanced public health strategies to address the causes of anemia, including better antenatal care, nutritional supplementation, and health education, to reduce the adverse outcomes for both mothers and infants.